The use of temporal artery ultrasound in the diagnosis of giant cell arteritis in routine practice. (8th June 2013) - Black, Rachel; Roach, Denise; Rischmueller, Maureen; Lester, Susan L.; Hill, Catherine L.
Abstract: Aim: The exact diagnostic role of temporal artery ultrasound (TAU) remains unclear. The aim of this study was to determine the sensitivity and specificity of a positive halo sign in patients undergoing TAU in a clinical setting, and to perform a review of existing evidence. Method: Patients who had undergone TAU at a single centre in Australia were included in the study. The presence or absence of a halo sign and whether it was unilateral or bilateral was determined retrospectively from radiology reports. Pathology results were used to determine which patients underwent a temporal artery biopsy and if the biopsy was positive or negative. A case note review was performed to determine presenting clinical features and if a clinical diagnosis of giant cell arteritis was made. The sensitivity, specificity and likelihood ratios of TAU compared to both biopsy and clinical diagnosis were calculated. Results: Fifty patients were identified as having had a TAU (28% male, mean age 69). When compared to biopsy‐proven cases, the sensitivity of a halo sign was 40%, specificity 81%, positive likelihood ratio 2.1 and negative likelihood ratio 0.7. When compared to clinical diagnosis, the sensitivity was 42%, specificity 94%, positive likelihood ratio 7.1 and negative likelihood 0.6. Conclusions: Sensitivity and specificity results were comparable to the literature. A halo sign may preclude the need for biopsy in cases of high clinical suspicion and contraindications to surgery. Biopsy remains necessary in most cases, irrespective of whether a halo sign is present.